Problems of diagnostics and treatment of uterine tube cancer (clinical case) - N. E. Levchenko; S. V. Mushtenko; M. V. Savostikova; T. I. Zakharova (ABV-press, 2016)
The clinical case of seldom found pathology - primary cancer of the uterine tube including at the same time both epithelial and sarcomatous component of a tumor is described. Data on a cancer of a uterine tube which, being a rare tumor are submitted, is morphologically similar to an ovary carcinoma. Predictively significant factors for this tumor are the disease stage, volume of residual tumoral masses, SA-125 indicators, and also as those the vascular invasion, degree of a differentiation of a tumor and age of patients are considered. On the basis of our supervision and clinical experience we came to a conclusion that this clinical case emphasizes not specificity of a current and complexity of timely diagnosis of a disease. Thus, an actual task is research of this problem for the purpose of improvement of quality of early diagnosis of primary cancer of uterine tube and use of new modern methods of treatment.